Improving Students’ Ability in Writing Procedure Text Throught Realia at the Seventh Grade SMPN 3 Ciruas - Mardiah, Mardiah (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
The objective of this research was to find out the process to teach students’ procedure text through Realia and find out whether Realia can improve students’ writing ability in learning procedure text. The Population was the ninth grade students of SMPN 3 Ciruas that consisted of 38 students as the sample. The researcher using mix method quanitative and qualitative by applying Class Action research (CAR) as a research methodology. The researcher used pre-test and post-test to collect the quantitative data. Meanwhile, the researcher used observation sheet, and documentation for collecting the qualitative data. This research was conducted in two cycles which consists two meetings in every cycle. The process teaching writing go on very well, the students enjoyed and had more active in every meeting. The students also could build self-confidence and collaborative in learning process because they study based on their experience. Furthermore, the usage of realia makes the class more fun, and the students are more interested in learning writing especially in writing procedure text, so it made the students’ writing ability was better than before it can be fun. The result, their fluency score in the first cycle, the average of pre-test was 51.78, and average post-test 1 was 69.78. For cycle 2, the average of post-test 2 was 79.89. So, the students score percentage from pre-test to post-test 1 was 18% and the percentage from post-test 1 to post-test 2 was 10.11%. The researcher found that the students got an improvement in writing skill especially in procedure text. In conclusion, Realia as a media of teaching learning process can improve students’ writing skill in procedure text.